Accompaniment of Making Research Articles and Publishing for Junior High School Teachers in Sambas and Malaysia Regions Borders - Rustiyarso Rustiyarso; Bistari Bistari; Tahmid Sabri (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2018)
For local teachers information on formal education, development is quite difficult. Teacher activities that support their professionalism are less conducive. One of the teacher's vessels in discussing or discussing materials in the lesson ie MGMP (Subject Teacher Consultative). The results of questionnaires and interviews (June 2012) revealed that many MGMP is not performing their activities properly. Several factors are expressed such as (1) more meeting material on routines, (2) difficult transportation, (3) funds; and (4) lack of motivation because it is considered to have no direct effect. During the 2012 academic year, MGMP Mathematics for Kecamatan Paloh performs only two meetings. While MGMP Matematika Sambas City is active almost every month. However, the focus of the meeting tends to routine the discussion of making common repetition questions together. Another case with the MGMP IPS, for the District of Paloh quite somewhat active but the focus of the study has not been right on target. Taking note of the above facts, it is necessary to have activities that provide freshness again and at once can be felt directly benefits such as the need for workshops presented expert and support the professionalism of teachers. In this activity, the PKM team coordinates with several MGMPs in Kecamatan Paloh and Kota Sambas. Activities undertaken are (1) conducting surveys to MGMP targets; (2) analyze survey findings; (3) design workshop activities coordinated with MGMP managers; (4) implementation of workshop, (5) process of making article writing; (6) meeting and presentation of accompaniment article; (7) selection and publication of articles to the targeted journal; (8) reporting.